Deformation and recrystallization texture and microstructure evolution of thin grain-oriented silicon steel sheets - BI Na; ZHANG Ning; YANG Ping (工程科学学报, 2015)
Combined with magnetic property measurements of thin grain-oriented silicon steel sheets annealed to different recrys-tallization stages, the deformation and recrystallization texture and microstructure evolution of the sheets was analyzed by using the electron back-scattering diffraction (EBSD) micro-texture analysis technique and X-ray diffraction texture analysis technique. The results show that the deformation texture transforms from {110}{001}to {111}{112} about the transverse direction. Meanwhile, it should be noticed that additional crystal rotation about RD which leads to the occurrence of a weak{001}{100} texture near the sheet surface appears in deformed grains, thus the origin of a cube recrystallization texture can be explained. As the annealing temperature increases, there occur abnormal grain growth and changes in magnetic properties, which are bound up with texture evolution including a beneficial {110} -{100}{001} texture and other weak texture components. Taking both abnormal grain growth and texture evolution into consideration, it is deduced that secondary and tertiary recrystallization occur. There exists crystallographic rotation about the{001} axis between different kinds of textural components at different recrystallization stages, so the recrystallization texture evolution of the sheets is believed to be driven by the growth dominance of grains having {100} rotational relationship with primary grains and the inhibition effect of the sharp Goss matrix. On the other hand, the abnormal growth of Goss grains induced by the strong advantage of {110} surface energy leads to a sharp Goss texture during tertiary recrystallization after annealing at high temperature for long time.